MENENTUKAN NILAI PERIODE, AMPLITUDO, FREKUENSI DAN MEMVISUALISASI GETARAN HARMONIK PADA PEGAS DALAM BENTUK GELOMBANG - Heri Rismawan; Muktamar Cholifah Aisiyah (Jurnal Fisika : Fisika Sains dan Aplikasinya, 2023)
Simple harmonic motion is motion back and forth regularly through an equilibrium point with the number of vibrations in every second always the same or constant. This experiment focuses on one example of an elastic object, namely a spring. The response of the spring to the force is indicated by the increase in the length of the spring. The background of this harmonic vibration experiment is to explain the process of harmonic vibration of a spring which is visualized in waves with the aim of explaining the harmonic vibration of a spring which is visualized in a wave. The data collection method in this experiment only used 1 load, namely 2 variations of springs (single spring and series spring) with a distance of 2 cm, 4 cm, and 6 cm. Different values ​​of A, y0, and c are obtained. From all the data that has been processed using the Orgin Arduino software application, it can be seen that the value of the amplitude is 0.46 cm-6.23 cm. The period value is 10.6 seconds-17.9 seconds and the frequency is 0.05 Hz-0.09 Hz. In addition, the initial phase value of -0.08 to -4.96 was also obtained. From the results of this experiment, the spring that has the largest amplitude value of 6.23 cm is a variation of the series spring with a deviation of 6 cm. While the spring which has the greatest period, frequency, and initial phase values ​​is the variation of spring 1 with a deviation of 4 cm. Based on the experimental results show that, the vibrations that occur in the spring are different in the form of waves. This is because the distance and the spring used during the experiment affect the shape of the waves that occur.